2020
DOI: 10.1155/2020/5480148
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Level of Serum C-reactive Protein Predicts Postoperative Delirium among Patients Receiving Cervical or Lumbar Surgery

Abstract: Objective. To explore the relationship between elevated serum C-reactive protein (CRP) level and postoperative delirium (POD). Methods. 206 patients scheduled to receive cervical or lumbar vertebra surgery under general anesthesia for more than 2 hours in a single medical center were observed and analyzed. Patients’ serum CRP, delirious status (using the confusion assessment method (CAM)), and delirious score (using the memorial delirium assessment scale (MDAS)) were examined before surgery and 1-2 days after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…Reasons for exclusion were no diagnosis by physician or research personnel (428 studies), no characterization of predisposing or precipitating factors (338 studies), retrospective study design (86 studies), not diagnosed by reference standard (108 studies), no multivariable model (43 studies), delirium assessment not conducted in person (25 studies), not cohort or case-control design (20 studies), sample included less than 50 patients (12 studies), abstract only (18 studies), cohort previously reported (3 studies), and pediatric population (1 studies). Ultimately, 315 studies…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reasons for exclusion were no diagnosis by physician or research personnel (428 studies), no characterization of predisposing or precipitating factors (338 studies), retrospective study design (86 studies), not diagnosed by reference standard (108 studies), no multivariable model (43 studies), delirium assessment not conducted in person (25 studies), not cohort or case-control design (20 studies), sample included less than 50 patients (12 studies), abstract only (18 studies), cohort previously reported (3 studies), and pediatric population (1 studies). Ultimately, 315 studies…”
Section: Resultsmentioning
confidence: 99%
“…Studies were conducted in 40 different countries, with the plurality in the United States (86 studies [27.3%]), followed by China (48 studies [15.2%]) and the Netherlands (24 studies [7.6%]). Most studies were prospective cohort studies (296 studies…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculate that this is due to the fact that we use the PSM method to control the confounding factors and eliminate the interference [ 29 ]. In the study of Ren et al, they found that the increase of CRP is the independent risk of POD [ 30 ]; the difference is that they use the change of CRP (values of serum CRP between before and after surgery) as a variable, rather than a simple preoperative CRP value. We believe that the cause of POD should be the increasing inflammatory reaction during operation, not the inflammatory state before operation, and some studies have also found proinflammatory factors in the cerebrospinal fluid of patients with postoperative delirium [ 31 ], so the increase of preoperative CRP (or ESR) does not prove that patients have the risk of POD, but attention should be paid to the dynamic fluctuation of inflammatory indexes in perioperative patients.…”
Section: Discussionmentioning
confidence: 99%
“…Literature Quality and Bias Evaluation. In this study, the cases included in the literatures [9,10,[14][15][16][17][18][19][20][21][22][23][24][25][26][27] were representative, the potential risk of bias was small, and some literatures did not describe the dropout cases in detail [22,23], but the overall quality score of all literatures was 7-9 points, with good quality, as shown in Table 2.…”
Section: Literature Quality Evaluation and Risk Of Biasmentioning
confidence: 99%